1997
DOI: 10.1007/s004649900296
|View full text |Cite
|
Sign up to set email alerts
|

Is it necessary to retrieve dropped gallstones during laparoscopic cholecystectomy?

Abstract: In conclusion, infected bile in combination with multiple stones increases the gross grading of adhesion and intraabdominal abscess formation. Thus, in cases with multiple stones and infected bile, the dropped stones should be retrieved and the peritoneal cavity should be copiously irrigated during laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…Intraabdominell zuru È ckbelassene Gallensteine ko È nnen zu Komplikationen wie Absceûbildung, Adha È sionen und Ileus fu È hren[2,5,11,27]. Zorluoglu et al konnten in einer experimentellen Arbeit mit Ratten zeigen, daû die Kombination von infizierten Steinen und Anzahl der zuru È ckbelassenen Konkremente die Absceû-und Adha È sionsrate erho È ht[28]. In einer Serie von Jones et al[7] kam es bei 33 % der laparoskopischen Cholecystektomien zu einer Gallenblasenperforation.…”
unclassified
“…Intraabdominell zuru È ckbelassene Gallensteine ko È nnen zu Komplikationen wie Absceûbildung, Adha È sionen und Ileus fu È hren[2,5,11,27]. Zorluoglu et al konnten in einer experimentellen Arbeit mit Ratten zeigen, daû die Kombination von infizierten Steinen und Anzahl der zuru È ckbelassenen Konkremente die Absceû-und Adha È sionsrate erho È ht[28]. In einer Serie von Jones et al[7] kam es bei 33 % der laparoskopischen Cholecystektomien zu einer Gallenblasenperforation.…”
unclassified
“…In an experimental study by Zorluglu et al [7], analysing the role of implanted gall stones inside the peritoneal cavity of rats with sterile or infected bile, the authors concluded that the combination of multiple stones and infected bile increases the chance of adhesions and intra-abdominal abscesses. Kimura et al[ 2] reported from their clinical study that peritoneal washings from patients with gall-bladder perforation were positive for bacteria in 37.9% of cases but only in 6.2% of patients without perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only a very small number of studies and research programs have been reported in which the relation between intraoperative complications during LC and the rate of postoperative adhesion formation is discussed. These were mainly experimental studies dealing with the problem of dropped gallstones [9,19].…”
Section: Discussionmentioning
confidence: 99%